Respuesta :
Answer:
StartFraction 1 Over 8 EndFraction
Step-by-step explanation:
[tex] \bigg( \huge{{6 {m}^{ - 1} {n}^{0} }} \bigg)^{ - 3} \\ \\ = \bigg( \huge{{6 {m}^{ - 1} \times 1 }} \bigg)^{ - 3} \\ \\ = \bigg( \huge{{ \frac{6}{m} }} \bigg)^{ - 3} \\ \\ = \bigg( \huge{{ \frac{m}{6} }} \bigg)^{3} \\ \\ = \bigg( \huge{{ \frac{3}{6} }} \bigg)^{3} \\ \\ = \bigg( \huge{{ \frac{1}{2} }} \bigg)^{3} \\ \\ = \huge{{ \frac{1}{8} }} \\ [/tex]
The value of the expression [tex](6m^{-1} n^{0})^{-3}[/tex] is one - eighth.
What is power and exponent?
"Power is a number which expressed as a base number raised to the exponent."
According to the question,
m= 3 and n = -5
Expression = [tex]( 6m^{-1} n^{0} )[/tex]
Substitute the value of m and n in the expression
Value of the expression = [tex](6[/tex] × [tex]3^{-1}[/tex] × [tex](-5)^{0}[/tex] [tex])^{-3}[/tex]
= [tex]\frac{1}{8}[/tex]
Hence the value of the expression [tex](6m^{-1} n^{0})^{-3}[/tex] is one - eighth.
Learn more about power and exponent here
https://brainly.com/question/15722035
#SPJ2